DESAIN RUANG DAN PENCAHAYAAN BUATAN UNTUK MENDUKUNG SUASANA KONTEMPLASI PADA GEREJA KATOLIK REGINA CAELI, JAKARTA - Ariani Mandala (ATRIUM: Jurnal Arsitektur, 2015)
Title: Space and Lighting Design to Support Contemplation Atmosphere in Regina Caeli Catholic Church, Jakarta The study examines how the light and space in the Church of Regina Caeli able to reinforce the presence of God?s impression and support contemplation?s atmosphere. The discussion reviewed by spatial elements (lobby/narthex, pulpit/nave, and sanctuary/chancel), enclosure elements (floors, walls, ceilings), and interior elements (furniture, decoration, and symbols). The lighting aspects explored are physical aspect (light source, technique, light distribution, colour, and level of light) and perception aspect (psychology of light). The study shows that the lighting support contemplation by emphasizing the sacred-secular space?s transition and strengthen the sacred space?s orientation. The contemplation is weakened due to the excessive number of liturgical symbols that blurring the people?s focus. As a pluriform church, Regina Caeli applying the combined effect of vertical and horizontal shape and space, but the lighting only emphasizes the horizontal effect that caused the impression of a church that is humane.